2020
DOI: 10.1371/journal.pone.0228133
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal microbiota development and the effect of early life antibiotics are determined by two distinct settler types

Abstract: The neonatal period, during which the initial gut microbiota is acquired, is a critical phase. The healthy development of the infant's microbiome can be interrupted by external perturbations, like antibiotics, which are associated with profound effects on the gut microbiome and various disorders later in life. The aim of this study was to investigate the development of intestinal microbiota and the effect of antibiotic exposure during the first three months of life in term infants. Fecal samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…In the long term, antibiotic therapy in infants and young children may have a significant impact on the process of microbiota development and on microbial programming of anti-allergic mechanisms later in life [29,30]. Table 1 presents a summary of studies showing the effect of antibiotic exposure in perinatal and early post-natal periods on the composition of intestinal microbiota [26,[31][32][33][34][35][36][37][38]. Studies in children from the age of 0 to 3 years showed that the microbiota of antibiotic-treated children was less diverse, with a lower abundance of the phylum Actinobacteria (with the genus Bifidobacterium), the genus Lactobacillus, Bacteroides, and had fewer stable bacterial communities in comparison with that in untreated children [38].…”
Section: Antibiotics Microbiota and Allergy Developmentmentioning
confidence: 99%
“…In the long term, antibiotic therapy in infants and young children may have a significant impact on the process of microbiota development and on microbial programming of anti-allergic mechanisms later in life [29,30]. Table 1 presents a summary of studies showing the effect of antibiotic exposure in perinatal and early post-natal periods on the composition of intestinal microbiota [26,[31][32][33][34][35][36][37][38]. Studies in children from the age of 0 to 3 years showed that the microbiota of antibiotic-treated children was less diverse, with a lower abundance of the phylum Actinobacteria (with the genus Bifidobacterium), the genus Lactobacillus, Bacteroides, and had fewer stable bacterial communities in comparison with that in untreated children [38].…”
Section: Antibiotics Microbiota and Allergy Developmentmentioning
confidence: 99%
“…Establishment of the microbiome during the neonatal period depends on multiple factors, including mode of delivery, breast versus formula feeding, gestational age, infant hospitalization, maternal diet and antibiotic use by the infant 14 , 15 . While antibiotics are beneficial for treating human bacterial infections, even short regimens can impact human gut microbial populations 16 18 and prolonged broad-spectrum antibiotic therapy can significantly alter the normal balance of beneficial bacteria 19 .…”
Section: Introductionmentioning
confidence: 99%
“…short regimens can impact human gut microbial populations [16][17][18] and prolonged broad-spectrum antibiotic therapy can significantly alter the normal balance of beneficial bacteria 19 .…”
mentioning
confidence: 99%
“…Exposure to intrapartum antibiotics for prevention of Group B streptococcal sepsis and/or due to cesarean section is extremely common and impacts the neonatal intestinal microbiota [ 47 , 48 ]. In addition to antibiotics [ 49 ], other medications commonly administered to mothers and/or infants that alter the intestinal microbiota include acid blocking agents [ 50 , 51 ], selective serotonin reuptake inhibitors, metformin and laxatives [ 52 , 53 ]. Recent demonstrations of altered infant microbiota with exposure to environmental toxins [ 54 , 55 ], maternal smoking [ 56 ], and proximity to furry animals [ 42 , 57 ] underscore the many factors affecting this community.…”
Section: Causes Of Neonatal Intestinal Dysbiosismentioning
confidence: 99%
“…In very preterm infants, the primary determinants of the composition of the intestinal microbiota are the post-menstrual age and age in weeks [ 34 , 35 ], however, multiple other factors are also influential including antenatal corticosteroids, mode of delivery, antibiotic exposure, feeding type, feeding tube dwell time and biofilms, gender, and stress [ 58 61 ]. Table 1 presents several examples of alterations in the infant fecal microbiota related to perinatal exposures [ 43 , 47 49 , 56 , 57 , 60 , 62 67 ].…”
Section: Causes Of Neonatal Intestinal Dysbiosismentioning
confidence: 99%